Synthesis and evaluation of novel inhibitors of 1-Deoxy-D-xylolose-5-phosphate reductoisomerase as potential antimalarials - Conibear, Anne Claire (Rhodes University, Faculty of Science, Department of Chemistry)
Malaria continues to be an enormous health-threat in the developing world and the emergence of drug resistance has further compounded the problem. The parasite-specific enzyme, 1-deoxY-D-xylulose-S-phosphate reductoisomerase (DXR), has recently been validated as a promising antimalarial drug target. The present study comprises a combination of synthetic, physical organic, computer modelling and bioassay techniques directed towards the development of novel DXR inhibitors. A range of 2-heteroarylamino-2-oxoethyl- and 2- heteroarylamino-2-oxopropyl phosphonate esters and their corresponding phosphonic acid salts have been synthesised as analogues of the highly active DXR inhibitor, fosmidomycin. Treatment of the heteroarylamino precursors with chloroacetyl chloride or chloropropionyl chloride afforded chloroamide intermediates, Arbuzov reactions of which led to the corresponding diethyl phosphonate esters. Hydrolysis of the esters has been effected using bromotrimethylsilane. Twenty-four new compounds have been prepared and fully characterised using elemental (HRMS or combustion) and spectroscopic (1- and 2-D NMR and IR) analysis. A 31p NMR kinetic study has been carried out on the two-step silylation reaction involved in the hydrolysis of the phosphonate esters and has provided activation parameters for the reaction. The kinetic analysis was refined using a computational method to give an improved fit with the experimental data. Saturation transfer difference (STD) NMR analysis, computer-simulated docking and enzyme inhibition assays have been used to evaluate the enzyme-binding and -inhibition potential of the synthesised ligands. Minimal to moderate inhibitory activity has been observed and several structure-activity relationships have been identified. In silica exploration of the DXR active site has revealed an additional binding pocket and information on the topology of the active site has led to the de novo design of a new series of potential ligands.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Antimalarials -- Development; Malaria -- Chemotherapy; Drug development; Enzyme kinetics; Phosphate esters